Analisis Pengelolaan Kas pada UMKM - Amaliyah, Fitri; Yasmin, Arifia; Hetika (Owner : Riset dan Jurnal Akuntansi, 2024)
Effective cashflow management is very important for the continuity and growth of Micro, Small, and Medium Enterprises (MSMEs). With good cash management, it will be able to avoid liquidity problems, be able to make the right strategic decisions and ensure business continuity in the long term. The purpose of this study is to find out the cash management of Convection MSMEs in Tegal Regency. The data collection method in this study is using observation and interviews. Meanwhile, the sampling technique uses random sampling of 9 MSMEs in the Adiwerna District area. The results of the study found that the cash management carried out by Convection MSME owners in the Tegal Regency area is still very minimal. This can be seen from the fact that most MSME owners have not planned, monitored or controlled cash. Of the MSMEs that manage cash, most have not done cash planning. In addition, the monitoring carried out on cash by most MSME owners is only limited to recording cash receipts and cash expenditures in a simple way, namely recording in books alone is not in accordance with applicable accounting standards. Furthermore, the control carried out by MSMEs is also only limited to not giving too much receivables to customers and carrying out a strategy of providing discounts when their business experiences a decline in sales. This is due to the lack of financial literacy knowledge in managing their finances, especially in compiling financial reports